2022
DOI: 10.1136/bmjopen-2021-056395
|View full text |Cite
|
Sign up to set email alerts
|

Association between control status of blood pressure and frailty among middle-aged and older adults with hypertension in China: a longitudinal study

Abstract: ObjectiveTo assess the association between blood pressure (BP) control and frailty among middle-aged and older populations with hypertension in China from 2013 to 2018.DesignProspective longitudinal study.SettingThis study analysed data from the China Health and Retirement Longitudinal Study, a nationally representative survey administered in 28 provinces of China.ParticipantsA total of 3254 participants diagnosed with hypertension previous to 2013 were taken into analysis. 1932 participants who were not frail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…No significant association of frailty with office, home and ambulatory BP was detected in this sample, suggesting that BP values probably show a weaker association with frailty in older hypertensive adults in comparison with other clinical variables. Indeed, some previous studies reported similar results, showing no cross-sectional association between BP and frailty status, particularly at advanced age [ 46 , 63 ]. However, it cannot be excluded that our findings might have been influenced by the limited sample size.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…No significant association of frailty with office, home and ambulatory BP was detected in this sample, suggesting that BP values probably show a weaker association with frailty in older hypertensive adults in comparison with other clinical variables. Indeed, some previous studies reported similar results, showing no cross-sectional association between BP and frailty status, particularly at advanced age [ 46 , 63 ]. However, it cannot be excluded that our findings might have been influenced by the limited sample size.…”
Section: Discussionmentioning
confidence: 66%
“…To date, few studies have analysed the prevalence of frailty in older patients with hypertension, providing highly variable proportions ranging from 3 to 68% according to the clinical setting and the adopted assessment tool [ 9 , 45 , 46 ]. In older adults participating in the HYVET and SPRINT studies, frailty status was identified using the FI and a left skewed distribution of scores was observed, with median values of 0.17 and 0.18, respectively [ 12 , 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis showed that systolic blood pressure greater than or less than 140 mmHg among frail people did not affect mortality, ordinary people with systolic blood pressure less than 140 mmHg are less likely to die ( 29 ). According to a newly published longitudinal study, those with poorly controlled blood pressure had a higher risk of becoming frail (HR = 1.96, 95% CI 1.49–2.56, p 0.001), and their frailty ratings were positively correlated with them (β = 0.015; 95% CI 0.011–0.019; p 0.001) ( 30 ). The 2019 Chinese Guideline for Hypertension in Older Persons, the European Society of Hypertension, the European Geriatric Medicine Society, and other organizations strongly underlined that frailty assessment is a crucial component of the proper therapy of hypertension in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…8 The relationship between BP and frailty was previously reported to be dependent on the age of the study population, 9 and it was inconsistent in a meta-analysis of general populations. 10 Hypertension in a middle-aged population was associated with an increased risk of frailty, 11 but, subjects >75 years with BP <110/75 mmHg were at an increased risk of frailty, 12 and lower BP was associated with a higher risk of frailty. 13 Additionally, there was no significant relationship to progression to frailty from prefrailty in a general population.…”
Section: Introductionmentioning
confidence: 98%